2006
DOI: 10.1007/s00425-006-0357-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photoreceptor currents and their sensitivity to the chemoeffector tryptone during gamete mating in Chlamydomonas reinhardtii

Abstract: Chlamydomonas reinhardtii Dangeard generates photoreceptor currents (PCs) upon light excitation. These currents play a key role in the signal transduction chain for photomotility responses. We have previously found that inhibition of PCs by tryptone occurs only in gametes that display chemotaxis toward this agent, and is not observed in chemotactically insensitive vegetative cells. Here we show that the sensitivity to tryptone is characteristic of gametes of both mating types, and examine the influence of game… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Peptone and tryptone are products of pancreatic digest of casein and are widely used as supplements to growth media for culti vation of microorganisms, including photosynthesis defi An early study [30] revealed that peptone attracts or repels, depending on the concentration, C. eugametos gametes. Similar data were also obtained for tryptone in C. reinhardtii [31]. Moreover, it has been established that vegetative cells of C. reinhardtii, unlike gametes, are insensitive to tryptone.…”
Section: Chemoreception and Signal Transductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Peptone and tryptone are products of pancreatic digest of casein and are widely used as supplements to growth media for culti vation of microorganisms, including photosynthesis defi An early study [30] revealed that peptone attracts or repels, depending on the concentration, C. eugametos gametes. Similar data were also obtained for tryptone in C. reinhardtii [31]. Moreover, it has been established that vegetative cells of C. reinhardtii, unlike gametes, are insensitive to tryptone.…”
Section: Chemoreception and Signal Transductionsupporting
confidence: 78%
“…2, c and f). Correlation between the time courses and concentration dependencies of chemotaxis towards tryptone and the suppression of photoreceptor currents by this agent has been found [31]. The data show that gamete specific inhibition of photoreceptor currents by tryptone is due to the activation of the signaling cascade involved in chemotaxis towards this agent, and that initial steps of transduction of photic and chemical stimuli involve common elements (Fig.…”
Section: Chemoreception and Signal Transductionmentioning
confidence: 87%
“…The light adaptation state of Chlamydomonas is also shifted towards an HL‐adapted state by increasing the cyclic AMP level with IBMX. Among other effects, IBMX induces expression of LHCSR3 , hyperphosphorylation of ChR1 in the dark, reduces the photoreceptor currents evoked by ChRs, and affects the phototactic sign and ciliary activity (Böhm et al, 2019; Boonyareth et al, 2009; Govorunova et al, 2007; Petroutsos et al, 2016; Saegusa & Yoshimura, 2015). The here observed long‐term reduction of the ChR1 starting levels by IBMX differs from its effect on LHCRS3 expression (Petroutsos et al, 2016) as it is not light‐dependent in wild‐type and ΔPHOT strains.…”
Section: Discussionmentioning
confidence: 99%